The little book of psychology - Hemmings, Jo (Big ideas, 2018)
The Little Book of Psychology clearly explains more than 100 groundbreaking ideas in this fascinating field of science. How does the brain remember faces? What makes us choose one decision over another? Where does language come from? With the use of powerful and easy-to-follow images, quotations from all the major thinkers, and explanations that are easily understandable, this book demystifies hard-to-grasp concepts and shows how these have shaped our knowledge of the human mind. All the schools of psychology are covered from cognitive to behavioural psychology making this ideal for students or for anyone with a general interest in this popular area. If you're fascinated by the human mind then The Little Book of Psychology will get you thinking in this brand new portable format.